As transformações recentes no mundo do trabalho e seus efeitos sobre as mulheres trabalhadoras latino-americanas - Silva, Juliana Franchi da (2006)
In this work he tried to understand the effects on the women hard-working Latin-Americans of the recent transformations happened in the world of the work. For so much, the analysis begins with the introduction of the feminine work starting from to industrial revolution, what brought consequences for every working class, in matter, for the women hard-working Latin-Americans that continue being explored and subdued by the capital. For her attainment the inductive and descriptive method was used in order to make possible the understanding of the bibliographical works that they based the investigation. This way, the research intended to do a rescue and a reflection of the conjuncture concerning the elements that favor the feminine insert in the world of the work and at the same time, it tried to observe the impediments that took it for a precarization of his workforce. Demonstrating like this, that in spite of the woman to have destroyed the old image of the traditional society, with the woman in her wife role, mother, administrator of the home, the children's educator, the feminine disadvantage still persists, therefore the woman still an unequal being is considered in the contemporary society. However, in spite of all of the difficulties faced by the woman, it is unquestionable that the incorporation of the same in the job market should be valued and fomented, therefore it is an important one aid for a larger economic growth, social and political of the nations.